Methodology Concept of Customer Profile Definition - Fürstner, Igor; Anišić, Zoran (International Journal of Industrial Engineering and Management, 2010)
In the twenty-first century, a company has to organize around the customer in order to be a successful and viable firm. Customers expect to get what they would like, with a side order of customization. This approach raises several questions that have to be answered, one of which is that despite nowadays customers are knowledgeable in general, they are still far from being experts that can really co-create a product or a service. Therefore, the fundamental challenge is to avoid the abortion of the configuration process by the customer. Based on problem analysis regarding customers’ involvement in the configuration process, the main areas of investigation to be considered are the minimization of the complexity experienced by the customers and the reduction of the cognitive overhead, considering not only the extent of choice, but also the lack of understanding about which solution meets their needs and also the uncertainties about the behavior of the supplier and the purchasing process. The paper presents one approach towards defining the appropriate customer profile that enabes the adaptation of the process of co-creation to different customers that suits each individual customer’s needs and limitations. Article history: Received (25.07.2010); Revised (26.09.2010); Accepted (02.10.2010)